Improving kangaroo care policy and implementation in the neonatal intensive care. Issue 4 (August 2015) - Moore, Hilary
Abstract This paper examines the current evidence based practice for providing kangaroo care in the Neonatal Intensive Care Unit (NICU). Additionally, this paper observes the effect of policy implementation and overcoming common obstacles to proper kangaroo care policy implementation. Implications for practicing kangaroo care are sustained through research supporting the initiation of kangaroo care in preterm infants; however, there are identifiable barriers preventing the skin-to-skin contact between mother and infant. The barriers commonly include insufficient nursing education, parent education, managerial support, and lack of a standard kangaroo care policy (Rodgers, 2013).